SYSTEMATIC LITERATURE REVIEW: PERAN AI SEBAGAI STIMULAN SRL SISWA DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA TAHUN 2024-2026 - Fahri Zulkarnain Pardamean Pane; Heni Pujiastuti; Ilmiyati Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This systematic literature review aims to analyze the role of Artificial Intelligence (AI) as a stimulus for students' self-regulated learning (SRL) and mathematical problem-solving abilities, given the persistent gap between the demand for 21st-century problem-solving skills and traditional instructional methods that make students passive. The study employs a Systematic Literature Review (SLR) following PRISMA guidelines, with article searches conducted on Google Scholar using Publish or Perish software and keywords combining